Effects of Polarized Training on Cardiometabolic Risk Factors in Young Overweight and Obese Women: A Randomized-Controlled Trial - Zapata-Lamana, Rafael; Henríquez-Olguín, Carlos; Burgos, Carlos; Meneses-Valdés, Roberto; Cigarroa, Igor; Soto, Claudio; Fernández-Elías, Valentín E.; García-Merino, Sonia; Ramirez-Campillo, Rodrigo; García-Hermoso, Antonio; Cerda-Kohler, Hugo (Frontiers in Physiology, 2018)
Introduction: Volume and intensity are major variables governing exercise training–mediated beneficial effects in both athletes and patients. Although polarized endurance training optimizes and maximizes physiological gains in highly trained individuals, its cardiometabolic protective-effects have not been established. The purpose of the present single site, randomized-controlled trial was to compare the effects of 12-weeks of high-intensity interval training (HIIT), moderate-intensity continuous training (MICT), and polarized volume training (POL) programs on cardiometabolic risk factors in young overweight and obese women. Materials and methods: A total of 64 overweight/obese young women (age 23.3 ± 3.8 y, body mass index 33.8 ± 3.8 kg/m2) were randomly assigned to four groups: control group (CTRL), polarized volume training group, moderate-intensity endurance training group, and high-intensity interval training group. The cardiorespiratory capacity, glycemic and lipid profiles, whole-body substrate utilization, and body composition were assessed before and after the intervention. Results: After the intervention, VO2peak and power output at VO2peak increased in all exercised-groups (time effect: p<0.0001). Power output at VT1 was increased only in the POL group compared to the CTRL group (p=0.019). Relative fold changes in fasting plasma glucose concentrations decreased only in POL group (p=0.002). Training induced a significant increase in relative fat oxidation in all the groups (time effect: p<0.001). Relative fat oxidation increased only in the POL group compared to the CTRL group (training effect: p=0.032). Conclusion: Twelve-weeks of polarized volume training showed overall superior effects on cardiorespiratory fitness, basal glycemic control, and substrate oxidation in comparison to MICT and HIIT training modalities. These data suggest that polarized volume training is an effective non-pharmacological treatment strategy for reducing cardiovascular disease risk factors in young overweight and obese women.